2021
DOI: 10.1021/acsomega.1c01607
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield and High-Efficiency Conversion of HMF to Levulinic Acid in a Green and Facile Catalytic Process by a Dual-Function Brønsted-Lewis Acid HScCl4 Catalyst

Abstract: Lignocellulosic biorefineries have received considerable attention for the purpose of producing high-value chemicals and materials. Levulinic acid (LA) is an important biomass-derived platform chemical that is produced from sugar-based biomass. Unfortunately, the catalysts reported thus far have shortcomings, such as expensive starting materials, complicated synthesis or purification operations, and a low LA yield under harsh reaction conditions. Herein, we develop a novel dual-functional catalyst, HScCl 4 , b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The acid-catalyzed decomposition of 5-HMF for the preparation of levulinic acid has been widely reported, but most of them were limited by low yields and deficient economic efficiency. Recently, a new strategy for the efficient green preparation of levulinic acid using bifunctional Brønsted Lewis acids (HScCl 4 ) as catalysts has been proposed by Yu et al [ 31 ]. In addition, the catalytic hydrogenation of 5-HMF using Pd/Al 2 O 3 catalysts afforded 2,5-tetrahydrofuran dimethanol (THFDM) with a 9:1 ratio of cis to trans structure [ 32 ].…”
Section: Bio-based Monomers From Lignocellulosementioning
confidence: 99%
“…The acid-catalyzed decomposition of 5-HMF for the preparation of levulinic acid has been widely reported, but most of them were limited by low yields and deficient economic efficiency. Recently, a new strategy for the efficient green preparation of levulinic acid using bifunctional Brønsted Lewis acids (HScCl 4 ) as catalysts has been proposed by Yu et al [ 31 ]. In addition, the catalytic hydrogenation of 5-HMF using Pd/Al 2 O 3 catalysts afforded 2,5-tetrahydrofuran dimethanol (THFDM) with a 9:1 ratio of cis to trans structure [ 32 ].…”
Section: Bio-based Monomers From Lignocellulosementioning
confidence: 99%
“…46 The rehydration of 5-(hydroxymethyl)furfural (HMF) followed by ring-opening leads to levulinic acid (LA) and an equimolar amount of formic acid as the byproduct. 47 Similarly, the hydrolysis of furfuryl alcohol (FAL), prepared by the catalytic hydrogenation of furfural (FF), leads to LA (Scheme 2). 48 LA is one of the most prominent carbohydrate-derived renewable chemical feedstock in the biorefinery realm.…”
Section: Hydrolysis Reactionsmentioning
confidence: 99%
“…A novel bifunctional catalyst, HScCl4, with high selectivity and efficiency was developed for converting HMF to LA. The DFT results showed that the synergistic catalytic effect generated by the acidic sites of HScCl4 significantly reduced the energy barriers of the reactants and intermediates, thus facilitating the conversion of HMF to LA (Liu et al 2021a).…”
Section: Cellulose Catalytic Conversion Mechanismmentioning
confidence: 99%